Inflammatory aneurysm of the C1 segment of the internal carotid artery linked to ipsilateral internal carotid artery occlusion due to otitis media: A Case Report and Literature Review - Xufeng Sun; Zhifeng Wen (Frontiers in Medicine, 2026)
Background Internal carotid artery occlusion (ICAO) is a very serious cerebrovascular disease, and ICAO caused by infection is extremely rare. We report a case of an extremely rare inflammatory aneurysm of the C1 segment of the ipsilateral internal carotid artery, caused by otitis media (OM), accompanied by ipsilateral ICAO. Case Presentation A 59-year-old woman presented to the emergency department with a 40-day history of fever and headache, which had worsened over the past 30 days and was accompanied by slurred speech and numbness in the right side of her face. Upon admission, a head and neck CTA revealed near-total occlusion of the right internal carotid artery (ICA) at the C1 segment with a massive distal aneurysm. The patient was diagnosed with severe OM with secondary intracranial infection by laboratory results, medical history and physical examination; cerebrospinal fluid (CSF) analysis was positive for human herpesvirus type 4 (EBV). Following multidisciplinary consultation, the patient's symptoms improved with medication adjustment and treatment with antibiotics and antiviral agents. Follow-up CTA demonstrated resolution of the aneurysm and progression of the ICA to long-segment occlusion. No ischemic neurological deficits were noted. CSF analysis showed marked reduction in EBV viral titer. At 6 months post-discharge, there were no indications of recurrence or new symptoms observed. Conclusion This case underscores an uncommon pathological route connecting OM, vasculitis, aneurysm development, and ICAO. The etiology and clinical progression of this ailment are exceedingly intricate; prompt identification and vigorous infection management are essential.